THERMODYNAMIC PROPERTIES CALCULATION USING A MULTIOBJECTIVE APPROACH IN ESTIMATING THE PARAMETERS OF THE GEOS3C EQUATION OF STATE - Silva, G. R.; Galo, T. M.; Soares Jr., A. M.; Oliveira, L. N. H. G. (Revista de Engenharia Térmica, 2023)
Since van der Waals’ first publication, a lot of equations of state have been proposed to represent the PVT behavior of pure compounds, as is the case with GEOS3C, which is a new form of generalized cubic equation of state that uses a temperature function dependent on three adjustable empirical parameters. In order to obtain the parameters that lead to the lowest errors of vapor pressure and saturated liquid volume predictions, it is possible to turn this problem into a multiobjective optimization problem. In this context, a modified MOPSO algorithm was employed. This method has the main advantage to provide a set of solutions that show the existing conflict in the attempt to minimize the properties of interest. Substances from different chemical families were used to evaluate the methodology proposed in this work and comparisons against experimental data were made. Results showed that the values obtained through multiobjective optimization for GEOS3C adjustable parameters provide better or equivalent predictions for all calculated thermodynamic properties. In addition, it was possible to observe a correlation between the parameters in the viable regions of the Pareto fronts: C1 assuming a constant value, whereas C2 and C3 are linearly dependent on each other